I want to be a wall. 1 - Shirono, Honami (Yen Press, 2022)
"Any love story aficionado will say that the key to a successful couple is intense desire for one another--but what if the characters in question are an asexual woman with a passion for Boys Love stories and a gay man whose heart forever belongs to his oblivious childhood friend? Although romance will never be in the cards for newlyweds Yuriko and Gakurouta, the bond blossoming between them promises to be a wonderful relationship--the likes of which neither has ever experienced before..." --